Semiconductor solar photocatalysts fundamentals and applications - Yu, Jiaguo; Li, Xin; Low, Jingxiang (Wiley-VCH, 2022)
Provides a timely overview of basic principles and significant advances of semiconductor-based photocatalysts for solar energy conversion Semiconductor Solar Photocatalysts: Fundamentals and Applications presents a systematic, in-depth summary of both fundamental and cutting-edge research in novel photocatalytic systems. Focusing on photocatalysts with vast potential for efficient utilization of solar energy, this up-to-date volume covers heterojunction systems, graphene-based photocatalysts, organic semiconductor photocatalysts, metal sulfide semiconductor photocatalysts, and graphitic carbon nitride-based photocatalysts. Organized into six chapters, the text opens with a detailed introduction to the history, design principles, modification strategies, and performance evaluation methods of solar energy photocatalysis. The remaining chapters provide detailed discussion of various novel photocatalytic systems such as direct Z-scheme and S-scheme photocatalysts, organic polymers, and covalent organic frameworks. This authoritative resource: Explains the essential concepts of solar energy photocatalysis and heterojunction systems for photocatalysis Reviews interesting structures and new applications of semiconductor photocatalysts Features contributions from an international panel of leading researchers in the field Includes extensive references and numerous tables, figures, and color illustrations Semiconductor Solar Photocatalysts: Fundamentals and Applications is valuable resource for all catalytic chemists, materials scientists, inorganic and physical chemists, chemical engineers, and physicists working in the semiconductor industry.
Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (John Wiley, viewed December 6, 2021)
Keywords: Photocatalysis; Solar energy; Photocatalyse; Énergie solaire; solar power